Statistical analysis plan for the ‘Efficacy of Nitric Oxide in Stroke’ (ENOS) trial - Bath, Philip M.W.; Houlton, Aimee; Woodhouse, Lisa J.; Sprigg, Nikola; Wardlaw, Joanna M.; Pocock, Stuart J. (SAGE Publications, 2014)
High blood pressure is common during the acute phase of stroke and is associated with a poor outcome. However, the management of high blood pressure remains unclear. The ‘Efficacy of Nitric Oxide in Stroke’ trial tested whether transdermal glyceryl trinitrate, a nitric oxide donor that lowers blood pressure, is safe and effective in improving outcome after acute stroke. Efficacy of Nitric Oxide in Stroke is an international multicenter, prospective, randomized, single-blind, blinded endpoint trial, with funding from the UK Medical Research Council. Patients with acute ischemic stroke or intracerebral hemorrhage and systolic blood pressure 140–220 mmHg were randomized to glyceryl trinitrate or no glyceryl trinitrate and, where relevant, to continue or stop prestrike antihypertensive therapy. The primary outcome is shift in modified Rankin Scale at three-months. Patients or relatives gave written informed (proxy) consent, and all sites had research ethics approval. Analyses will be done by intention to treat. This paper and attachment describe the trial’s statistical analysis plan, developed prior to unblinding of date. The statistical analysis plan contains design and methods for analyses, and unpopulated tables and figures for the two primary publications and some secondary publications. The database will be locked in late February 2014 in preparation for presentation of the results in May 2014. The data from the trial will improve the precision of the estimates of the overall treatment effects (efficacy and safety) of results from completed trials of blood pressure management in acute stroke, and provide the first large-scale randomized evidence on transdermal glyceryl trinitrate, and of continuing (vs. stopping) prestroke antihypertensive medications, in acute stroke.